2015
DOI: 10.1007/s00296-015-3274-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the association with fatigue and sleep in Danish patients with rheumatoid arthritis

Abstract: The aim of this study was to examine physical activity behavior in patients with rheumatoid arthritis and to identify potential correlates of regular physical activity including fatigue, sleep, pain, physical function and disease activity. A total of 443 patients were recruited from a rheumatology outpatient clinic and included in this cross-sectional study. Physical activity was assessed by a four-class questionnaire, in addition to the Physical Activity Scale. Other instruments included the Multidimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 57 publications
9
27
1
1
Order By: Relevance
“…Nevertheless, when we compared women who did and did not meet the PA recommendations (ie, 150 minutes/week of MVPA in bouts ≥10 minutes), we observed that those who did, presented a better SQ global score. For the remaining PA intensity levels, in contrast with our findings, a study performed in rheumatoid arthritis patients and others in young adults Kakinami et al did not find an association between PA and sleep. To note is that both studies assessed PA levels by questionnaires, whereas we have employed objectively measured PA. Andrews et al observed that, in patients with chronic pain, high‐intensity activities and high fluctuations in PA were associated with poorer sleep at night.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, when we compared women who did and did not meet the PA recommendations (ie, 150 minutes/week of MVPA in bouts ≥10 minutes), we observed that those who did, presented a better SQ global score. For the remaining PA intensity levels, in contrast with our findings, a study performed in rheumatoid arthritis patients and others in young adults Kakinami et al did not find an association between PA and sleep. To note is that both studies assessed PA levels by questionnaires, whereas we have employed objectively measured PA. Andrews et al observed that, in patients with chronic pain, high‐intensity activities and high fluctuations in PA were associated with poorer sleep at night.…”
Section: Discussioncontrasting
confidence: 99%
“…In children, this relationship has not been reported previously, but our finding corresponds with results found in adults with RA [41, 42]. The relationship between PAL and fatigue in RA patients appeared to be bidirectional; low PAL resulted in fatigue, and fatigue acted as a barrier to being active [41, 42]. Exercise capacity was correlated with fatigue but did not retain significance in the prediction model, indicating that factors other than exercise capacity play a role in the feeling of fatigue.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Our results were corresponded with previous research of RA patients such as that in the Netherlands and Denmark [51, 52]. Similar research has never been conducted in China, sot no comparison may presently be made in the same population.…”
Section: Discussionsupporting
confidence: 92%